Relative Contribution of Th1 and Th17 Cells in Adaptive Immunity to Bordetella pertussis: Towards the Rational Design of an Improved Acellular Pertussis Vaccine. - MCLOUGHLIN, RACHEL; LAVELLE, EDWARD; MILLS, KINGSTON; SUTTON, CAROLINE; HIGGINS, SARAH; ALLEN, AIDEEN (My University, 2013)
Whooping cough caused by Bordetella pertussis is a re-emerging infectious disease despite the introduction of safer acellular pertussis vaccines (Pa). One explanation for this is that Pa are less protective than the more reactogenic whole cell pertussis vaccines (Pw) that they replaced. Although Pa induce potent antibody responses, and protection has been found to be associated with high concentrations of circulating IgG against vaccine antigens, it has not been firmly established that host protection induced with this vaccine is mediated solely by humoral immunity. The aim of this study was to examine the relative contribution of Th1 and Th17 cells in host immunity to infection with B. pertussis and in immunity induced by immunization with Pw and Pa and to use this information to help rationally design a more effective Pa. Our findings demonstrate that Th1 and Th17 both function in protective immunity induced by infection with B. pertussis or immunization with Pw. In contrast, a current licensed Pa, administered with alum as the adjuvant, induced Th2 and Th17 cells, but weak Th1 responses. We found that IL-1 signalling played a central role in protective immunity induced with alum-adsorbed Pa and this was associated with the induction of Th17 cells. Pa generated strong antibody and Th2 responses, but was fully protective in IL-4-defective mice, suggesting that Th2 cells were dispensable. In contrast, Pa failed to confer protective immunity in IL-17A-defective mice. Bacterial clearance mediated by Pa-induced Th17 cells was associated with cell recruitment to the lungs after challenge. Finally, protective immunity induced by an experimental Pa could be enhanced by substituting alum with a TLR agonist that induces Th1 cells. Our findings demonstrate that alum promotes protective immunity through IL-1 b -induced IL-17A production, but also reveal that optimum protection against B. pertussis requires induction of Th1, but not Th2 cells
PUBLISHED
Keywords: Bordetella pertussis, whooping cough; Bordetella pertussis, whooping cough; Immunology, Inflammation & Infection